ANALISIS KERUGIAN EKONOMIS DAN PEMETAAN SEBARAN SERANGAN RAYAP PADA BANGUNAN SMA DAN SMK KOTA PEKANBARU - Frieda Sitepu; Luthfi Hakim; Yunus Afifuddin (Program studi Kehutanan USU, 2015)
Building planning always take into two important aspects related that is the strength and durability. Related to the strength , the structure of the building is planned based on the load to occur and the power structure of the materials used. The tendency of the danger of attacked by termites in buildings including residential function at this point is getting higher. This study intend to get the value of economic losses termite attack, and get the information types and the spread of termites that attack the buildings of Senior High School and Vocational High School in Pekanbaru. The research was conducted on July until August 2014. The method was used is direct observation and interviews. The results mapped with GIS applications. The results showed that 64% of senior school building have small damage and 36% of schools included in the moderate damage. Termite species found are a type of dry wood termites (Cryptotermes cynocephalus) and Termite soil (Microtermes inspiratus) Keywords: Termites, economic losses, school buildings, GIS